Strategi Optimalisasi CWLS Sebagai Tombak Ekonomi Indonesia: Indonesia - Fathmah Hanum; Saiful Bakhri (Tasharruf : Journal of Islamic Economics and Business, 2024)
CWLS is a fintech platform based on digital financial applications, which has entered the digital era through a website released by the Ministry of Finance. This website focuses on information about cash waqf, CWLS could be a solution for Indonesia's economic stability, but there are still many people, especially Muslim communities, who know about CWLS. This study wants to examine strategies that would be able to bring CWLS to greater existence and be better known to the wider community. The method used in this research is a qualitative method so that it explains more about the research results related to the strategies used to develop CWLS. The results of this research show that CWLS is able to appear and exist in the global realm if it has contemporary marketing, and also targets most web users, namely gen-z, as well as using CWLS more creatively so that it has more real influence in society.